2009
DOI: 10.1124/mol.108.050716
|View full text |Cite
|
Sign up to set email alerts
|

Phenylephrine-Induced Cardiomyocyte Injury Is Triggered by Superoxide Generation through Uncoupled Endothelial Nitric-Oxide Synthase and Ameliorated by 3-[2-[4-(3-Chloro-2-methylphenyl)-1-piperazinyl]ethyl]-5,6-dimethoxyindazole (DY-9836), a Novel Calmodulin Antagonist

Abstract: The pathophysiological relevance of endothelial nitric-oxide synthase (eNOS)-induced superoxide production in cardiomyocyte injury after prolonged phenylephrine (PE) exposure remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…To determine whether PEP19 induced by hyper trophic stress participates in the pathological process of cardiac hypertrophy, PEP19 was transfected into rat neonatal cardiomyocytes and its effect on cardiac hypertrophy and related cell signaling were addressed in the intact cardiomyocytes. Recently we reported that a novel antagonist of calmodulin inhibits the various calmodulindependent enzymes in a competitive manner and exerts a powerful cardioprotective action during the process of cardiac hypertrophy (35,36). On the other hand, PEP19 inhibited apoptosis in PC12 cells and protected HEK293T cells against death due to Ca 2+ overload (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether PEP19 induced by hyper trophic stress participates in the pathological process of cardiac hypertrophy, PEP19 was transfected into rat neonatal cardiomyocytes and its effect on cardiac hypertrophy and related cell signaling were addressed in the intact cardiomyocytes. Recently we reported that a novel antagonist of calmodulin inhibits the various calmodulindependent enzymes in a competitive manner and exerts a powerful cardioprotective action during the process of cardiac hypertrophy (35,36). On the other hand, PEP19 inhibited apoptosis in PC12 cells and protected HEK293T cells against death due to Ca 2+ overload (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…7% FBS High serum media stimulates hypertrophic growth through a different pathway by use of growth factors and glucose contained within the media (Ren et al, 2003). Our study did not seek to test the differences in GATA4 activation or CARP levels between the two hypertrophic stimuli, however several previous studies have shown that PE is a relatively stronger hypertrophic-inducing agent (Vara et al, 2003;Lu et al, 2009).…”
Section: Aim Onementioning
confidence: 99%
“…Importantly, DY-9836, an N-de-alkylated form of DY-9760e and active metabolite, promoted neuroprotective and cardioprotective effects against cardiac hypertrophy induced by endothelin-1 and angiotensin II (36,45). We also addressed an inhibitory effect of DY-9836 on uncoupling of eNOS and O 2…”
Section: Therapeutic Perspectivementioning
confidence: 99%